Celebrity Endorsement on Buying Interest Through Consumer Trust - Rahma, Ulva Nuraulya; Yendra, Yendra; Marihi, La Ode (Advances in Business & Industrial Marketing Research, 2025)
Purpose: This study aims to assess the influence of celebrity endorsement on the purchase intention of Implora beauty products and analyze the mediating role of consumer trust. Research Design and Methodology: The research employs a quantitative explanatory design. Data were collected through questionnaires distributed to 109 respondents, students using Implora products at the Faculty of Economics and Business, Universitas Yapis Papua. The data analysis was performed using Structural Equation Modeling (SEM) with AMOS 24 software. Findings and Discussion: The findings indicate that celebrity endorsement does not have a significant direct effect on purchase intention but has a substantial indirect impact through consumer trust. Consumer trust strongly mediates between celebrity endorsement and purchase intention, supported by the significant results of the Sobel test. These findings imply that marketing strategies involving celebrities should emphasize building consumer trust and focusing on product quality and brand image. Implications: The study recommends further research on cultural contexts and different product types to gain deeper insights into celebrity endorsement, consumer trust, and purchase intention dynamics.